Aplikasi Timing Kejuaraan Nasional Rally dan Sprint Rally Berbasis Web - Marvil Dondokambey; Lily Puspa Dewi; Justinus Andjarwirawan (Jurnal Infra, 2019)
These days, the organizational activities in the Indonesian Rally and Rallysprint Championship – including timing process are still done manually, and that means the organizers have to work harder to process all these data. One of the consequences is people are having difficulities on following the event wherever they are because lack of concrete source to give all the updates. Because of that, web-based information system have to be made.Basically the system are divided into two – admin and guest website. Administrative rally organizer, media officer and timekeeper have their respective admin site. Second are the website, which show all these data for the public. This system use PHP, MySQL and Laravel to do all these data operation process.Data are organized with controller as access road between program and database, and also used to save all the function, to make sure that aren’t fill the web script. The timing system are done manually, where a timekeeper would stand by on the end of each SS to input all timing data.Overall, this system are running smoothly, although there are many room for improvements, while the data are could be seen on the admin site and the website. In other side, the survey respondent are satisfied with this system.